2009
DOI: 10.4314/eajph.v5i3.39000
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors For Perinatal Mortality In Arua Regional Referral Hospital, West Nile, Uganda

Abstract: Background In low-income countries, the majority of neonatal deaths occur during the perinatal period. The fourth millennium development goal of reducing child mortality cannot therefore be met without substantial reduction in perinatal deaths. Objective To investigate the risk factors for perinatal mortality in Arua regional referral hospital, West Nile region. Methods We conducted a facility based unmatched case-control study at Arua Regional Referral hospital during January-March 2006. A total of 60 new cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…The finding of a higher risk of perinatal mortality among this category of women could be as a result of having to commute longer distances to assess antenatal care and intrapartum care services at the health facilities compared to those who lived within the area council thus making accessibility of antenatal and delivery services more difficult. The findings of this study corroborate the findings of the study in Abuja [36]and that of Akello et al [45].who found an increased risk of perinatal death among babies whose mothers travelled greater distances to access care [67].…”
Section: Discussionsupporting
confidence: 91%
“…The finding of a higher risk of perinatal mortality among this category of women could be as a result of having to commute longer distances to assess antenatal care and intrapartum care services at the health facilities compared to those who lived within the area council thus making accessibility of antenatal and delivery services more difficult. The findings of this study corroborate the findings of the study in Abuja [36]and that of Akello et al [45].who found an increased risk of perinatal death among babies whose mothers travelled greater distances to access care [67].…”
Section: Discussionsupporting
confidence: 91%
“…However, a similar study reported lower hazard rates in males compared to females in Niger. In addition, studies by Ayiko [31], Ettarh and Kimani [32] and Nasejje et al [33] pointed out that the sex of a child (female) reduces the risk of experiencing child mortality before the fifth birthday.…”
Section: Discussionmentioning
confidence: 99%
“…The human development and poverty indices in the northern region of Uganda including in the West Nile district of Arua are appealing. The district health indices are poor with high under five mortality rate (U5MR) and infant mortality rate (IMR) of 240 and 100 per 1000 live births compared to the national figure of 152 and 88 respectively (Akello et al, 2008)…”
Section: Study Areamentioning
confidence: 99%